A “secular” Malaysia? Toward an alternative democratic ethos - Ahmad, Khairil Izamin (IIUM Press, 2013)
Abstract: This article intervenes in the discourse that calls for the establishment of a secular state in Malaysia. Proponents argue that a secular state, with its principle of state neutrality in religious matters, would be most suited to oversee society’s democratic exchanges. The article traces the proposal’s affinities to theoretical debates on issues concerning pluralism, and argues that a secular regime may not be as neutral as proponents would make it to be, even if it transpires in a deontological form. The mistake with such work of reform lies in its preoccupation with kick-starting its efforts by making strong philosophical claims, which may well stifle, rather than further the interests of the plural society. The article argues that a more modest work of reform is possible, by way of exploring what existing infrastructures can do to help foster productive democratic exchanges, without having to foreclose the terms of engagements. The article concludes with a call for the cultivation of a novel set of civic virtues that would create positive democratic ethos.